Mortality-risk valuation, age and cause of death: out-of-hospital cardiac arrest - Björn Sund (University of Oslo, 2017)
Economic evaluation of policies regarding out-of-hospital cardiac arrest (OHCA) is important. The value of a statistical life (VSL) for OHCA victims is the most important component in a cost-benefit analysis of interventions that have the possibility to reduce mortality from this cause. This value is not known. We use responses to a national Swedish mail survey, based on the stated-preference technique to directly elicit individuals' hypothetical willingness to pay for a reduced risk of dying from OHCA. A lower-bound estimate of VSL for OHCA would be in range of SEK 30 to 50 million. The value is found to be higher than for comparable VSL estimates from the transport sector, even though individuals who suffer OHCAs are generally older and less healthy than people who die in road traffic accidents. The results indicate that it is not an overestimation to use the 'baseline' VSL value from the transport sector (SEK 24 million) in cost-benefit analysis of OHCA policy decisions and that the cause of death is important when examining willingness to pay for death risk reductions. We do not support a general declining VSL due to the age of the victims, i.e. a 'senior death discount', for this cause of death. Published: Online January 2017. In print December 2017.